PENURUNAN POLUSI TIMBAL OLEH JALUR HIJAU TANJUNG (Mimusops elengi Linn) DI TAMAN MONAS JAKARTA PUSAT [Decreasing Lead Pollution by Tanjung (Mimusops elengi Linn) Green Belt in Taman Monas, Central Jakarta] - Lindri Suyanti; Siti Badriyah Rushayati; Rachmad Hermawan (Media Konservasi, 2008)
Lead (Pb) concentration in the air emitted by fuel combustion from motor vehicles could be reduced by city green belt through the absorption and adsorption processes. The study was conducted to know the capability of tanjung green belt in Taman Monas in reducing lead (Pb) concentration emitted by motor vehicles fuel combustion. Pb concentration was measured using gravimetric method and analyzed using AAS (Atomic Absorption Spectrophotometer). The study showed that tanjung stand with 141 tree individuals in 13 rows were able to reduce Pb concentration with reduction rate of 0.26 μg/m3 in the morning, 0.30 μg/m3 in the day time, and 0.41 μg/m3 in the afternoon. Lead concentration in the air would increase with the increase of motor vehicles density. The green belt in Taman Monas could repair micro climate by reducing environmental temperature and increasing humidity.Keywords: Lead (Pb), green belt, tanjung (Mimusops elengi Linn), pollution